Survival of patients co-infected with HIV and SARS-CoV-2 at the Gaffrée and Guinle University Hospital (Research, Society and Development, 2024)
Background: In Brazil, COVID-19 has caused 702,492 deaths by May 2023, overwhelming healthcare systems. SARS-CoV-2/HIV co-infection has been little studied to date, but it has been observed that the presence of comorbidity was responsible for a poor prognosis of COVID. Main goal:  To estimate the survival of a cohort of patients co-infected with SARS-CoV-2 and HIV/AIDS who were admitted to the Gaffrée e Guinle University Hospital (HUGG). Methodology: Retrospective observational epidemiological study of a cohort of HIV patients co-infected with SARS-CoV-2 who were hospitalized at HUGG – EBSERH Network - between February 2020 and July 2022. Data collection occurred through medical record analysis. Inclusion criteria were: age over 18 years, all HIV infection statuses. Results: Of the 37 participants, 68% were male, 35.1% had been diagnosed with HIV for more than 10 years; 70.3% showed good adherence to antiretroviral therapy. Of the total, 64.9% had multimorbidities, and in 21.6%, one of the comorbidities was related to the respiratory system. The study population was prone to progress to the severe form, as 56.8% presented symptoms of SARS and 29.7% of the patients died. People living with HIV and high viral load are more susceptible to death, and changes in chest tomography presented a 28-fold greater risk of death. Conclusion: Presence of ground glass, male gender and increased viral load predisposed patients to death.